Testing the association of resting‐state functional connectivity of the hippocampus and prefrontal cortex with AD‐vulnerable executive functions in periadolescent children. (20th December 2022) - Zatkalik, Abigail L; Phipps, Connor J; Ramirez, Meghan K; Sexton, Jennifer N; Heller, Abi; Behm, Lillian; Nickolas, Kristen; Maerlender, Arthur C.; Phatak, Vaishali S; Cramer, Justin A.; Blair, James; Murman, Daniel L; et al.
Abstract: Background: Alzheimer's disease (AD) is an insidious neurodegenerative disease that is frequently associated with deficits in both memory and executive functions (EFs). EFs consist of a diverse range of cognitive processes, including inhibition, working memory, and cognitive flexibility. In AD and other disorders, dysfunction in EFs can result in attention deficits, decreased inhibition, and impaired decision‐making abilities. EFs have been historically linked to the prefrontal regions of the brain, but recent studies of brain networks and their functional connectivity have broadened these links to include brain regions such as the hippocampus (Hc). Building upon prior work, the current project investigated the association between decision making and hippocampal resting state functional connectivity (rs‐FC) in periadolescent children. Method: A cohort of healthy periadolescent children aged 8‐13 (N = 80) was sampled from the ongoing NIA‐funded Polygenic Risk of Alzheimer's Disease in Nebraska Kids (PRANK) study. PRANK participants completed an array of cognitive and behavioral measures, in addition to an MRI of the brain. Decision making ability was assessed via the NIH Toolbox Dimensional Change Card Sorting (DCCS) task. The rs‐FC between the Hc and regions of the prefrontal cortex (PFC) was measured, and its covariance with DCCS was assessed. Result: rs‐FC of the Hc covaried with performance on the DCCS in the left dorsolateral prefrontal cortex (dlPFC) and dorsal anterior cingulate cortex (dACC). These anatomical regions are in line with larger intrinsic brain networks, such as the frontoparietal network (FPN) and the cingulo‐opercular network (CON). Conclusion: These preliminary results suggest the Hc is associated with anatomical regions and intrinsic brain networks that are important for EFs. A better characterization of the process by which EF occurs within the brain may drive further research that can assess ways to limit the decline of these cognitive abilities associated with healthy aging or brain pathology such as AD.